Safe spaces? A social-ecological perspective on student perceptions of safety in the environment of the school canteen. Issue 1 (2nd January 2020) - Horton, Paul; Forsberg, Camilla
ABSTRACT: Background Research suggests that negative peer interactions that compromise student safety and wellbeing often occur in spaces at school that are not easily visible, not adequately monitored, overcrowded and/or relatively unstructured. In a large online survey conducted in Swedish schools by the anti-bullying organisation, Friends, a small proportion of students indicated that they felt unsafe in the school canteen and responded to a question about why they felt unsafe there. As the canteen is often reported to be a space where negative peer interactions, such as harassment, bullying and other forms of school violence, occur, but little is known about why negative peer interactions occur there, we were particularly interested in exploring why some students perceived their school canteen to be an unsafe space. Purpose Taking a social-ecological perspective, our aim was to investigate why students reported feeling unsafe in the environment of the school canteen. Method In order to investigate this question, we analysed 1, 547 responses from students in Swedish schools in grades 3–6 (ages 9–12). The responses were from the anti-bullying organisation Friends' online questionnaires from 2011 to 2016. In the responses, students who indicated that they felt unsafe in the school canteen explained why they felt this way. Data were analysed qualitatively, using a six-step thematic approach. Findings The analysis identified four key themes: Space constraints, Time restrictions, The risk of social blunders and The negative actions of others . We discuss the findings in terms of the macrosystem, exosystem, mesosystem and microsystem. Conclusions In matters of student safety and wellbeing, we argue that it is not only important to consider the social context, but also how that context is interconnected with environmental and structural elements.